An alternative polysaccharide uptake mechanism of marine bacteria - Reintjes, Greta; Arnosti, Carol; Fuchs, Bernhard M; Amann, Rudolf (The ISME Journal, 2017)
Heterotrophic microbial communities process much of the carbon fixed by phytoplankton in the ocean, thus having a critical role in the global carbon cycle. A major fraction of the phytoplankton-derived substrates are high-molecular-weight (HMW) polysaccharides. For bacterial uptake, these substrates must initially be hydrolysed to smaller sizes by extracellular enzymes. We investigated polysaccharide hydrolysis by microbial communities during a transect of the Atlantic Ocean, and serendipitously discovered—using super-resolution structured illumination microscopy—that up to 26% of total cells showed uptake of fluorescently labelled polysaccharides (FLA-PS). Fluorescence in situ hybridisation identified these organisms as members of the bacterial phyla Bacteroidetes and Planctomycetes and the gammaproteobacterial genus Catenovulum . Simultaneous membrane staining with nile red indicated that the FLA-PS labelling occurred in the cell but not in the cytoplasm. The dynamics of FLA-PS staining was further investigated in pure culture experiments using Gramella forsetii , a marine member of Bacteroidetes . The staining patterns observed in environmental samples and pure culture tests are consistent with a ‘selfish’ uptake mechanisms of larger oligosaccharides (>600 Da), as demonstrated for gut Bacteroidetes . Ecologically, this alternative polysaccharide uptake mechanism secures substantial quantities of substrate in the periplasmic space, where further processing can occur without diffusive loss. Such a mechanism challenges the paradigm that hydrolysis of HMW substrates inevitably yields low-molecular-weight fragments that are available to the surrounding community and demonstrates the importance of an alternative mechanism of polysaccharide uptake in marine bacteria.